La idea de Cruzada en el liber de Passagio de Ramón Llull - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 2004)
This paper wants to elucidate Ramon Lull's idea of Crusade. In the first place the article analyzes some historical facts that can be held as the medieval origins of the Crusade. It links the Crusade with the rooted practices of peregrinatio and passagium and also shows the presence of these in Lull's description of specific military tactics to fight against the pagans, an idea that is for the first time fully developed by Lull and that must also be understood in the context of the recent fall of Acre. To this kindled defense of the use of strength the author attributes the originality of the Liber de Passagio, at the same time that he sees in it the beginning of a new period in Lull's thought. The article also frames the Liber de Passagio in the context of the current papal policy, which implied the use of Crusade for the purposes of that policy, and links it with other previous and contemporary treatises on the Crusade.
Fil: Domínguez Reboiras, Fernando. Universidad de Friburgo. Raimundus-Lullus-Institut; Alemania.
Keywords: RELIGIÓN; GUERRA; CRUZADAS; RELIGIÓN CRISTIANA; UNIVERSIDAD DE FRIBURGO; LLULL, RAMÓN; LIBER DE PASSAGIO, RAMÓN LLULL